From business information literacy to decision-making, problem solving and innovation - Capinzaiki Ottonicar, Selma L. [UNESP]; Pomim Valentim, Marta L. [UNESP]; Bouthillier, France (Cherkas Global University Press, 2021)
In the international literature, business information literacy refers to information literacy in the business context. Most of the research in this field focuses on university libraries, thus there is a gap in the literature with respect to business information literacy in industry and competitive organizations. The purpose of this paper is to investigate the state of the art about business information literacy, and it aims to identify how researchers have studied business information literacy in businesses. The method is a systematic literature review in international scientific databases. After the analysis of the systematic literature protocol, we included 26 papers that discuss business information literacy. These papers show that business information literacy research focuses on business management libraries and related fields. This paper concludes that libraries contribute to business management curricula, and students can develop critical thinking and lifelong learning. Similarly, members of business organizations can use business information literacy to develop critical thinking for decision-making and problem-solving.
Keywords: Business information literacy; Business management libraries; Business people’s lifelong learning; Critical thinking; Information literacy